Psychometric properties of time attitude scores in young, middle, and older adult samples. (October 2016) - Mello, Zena R.; Zhang, Jia Wei; Barber, Sarah J.; Paoloni, Victoria C.; Howell, Ryan T.; Worrell, Frank C.
Abstract: In an effort to provide a measure of time perspective that can be used across the life-span, we examined the psychometric properties of the Adolescent Time Inventory-Time Attitude Scale (ATI-TA; Mello & Worrell, 2007) in three independent samples of young ( N = 388), middle ( N = 201), and older adults ( N = 189). Results provided strong psychometric evidence that the ATI-TA can be used appropriately with individuals across adolescence and adulthood. Specifically, internal consistency estimates indicated that scores on the six subscales (Past Positive, Past Negative, Present Positive, Present Negative, Future Positive, & Future Negative) were reliable across the three samples. Confirmatory factor analyses showed that the theorized six-factor structure had acceptable fit and fit the data better than alternate models. Subsequent analyses provided support for invariance across young, middle, and older adults. Overall, these results show that the ATI-TA yields reliable scores and a valid structure across adulthood and can be used to measure time perspective throughout the life-span. Highlights: The Adolescent Time Inventory-Time Attitude Scale may be used across adulthood. Positive and negative feelings about the past, present, and future were measured. Internal consistency estimates indicated that the subscales were reliable. Confirmatory factor analyses supported the theorized six-factor structure. The Scale was invariant across young, middle, and older adult groups.